Hydroxychloroquine with or without Azithromycin in Mild-to-Moderate Covid-19 - Cavalcanti AB; Zampieri FG; Rosa RG; Azevedo LCP; Veiga VC; Avezum A; Damiani LP; Marcadenti A; Kawano-Dourado L; Lisboa T; Junqueira DLM; de Barros e Silva PGM; et al. (Massachusetts Medical Society, 2020)
BACKGROUND: Hydroxychloroquine and azithromycin have been used to treat patients with coronavirus disease 2019 (Covid-19). However, evidence on the safety and efficacy of these therapies is limited. METHODS: We conducted a multicenter, randomized, open-label, three-group, controlled trial involving hospitalized patients with suspected or confirmed Covid-19 who were receiving either no supplemental oxygen or a maximum of 4 liters per minute of supplemental oxygen. Patients were randomly assigned in a 1:1:1 ratio to receive standard care, standard care plus hydroxychloroquine at a dose of 400 mg twice daily, or standard care plus hydroxychloroquine at a dose of 400 mg twice daily plus azithromycin at a dose of 500 mg once daily for 7 days. The primary outcome was clinical status at 15 days as assessed with the use of a seven-level ordinal scale (with levels ranging from one to seven and higher scores indicating a worse condition) in the modified intention-to-treat population (patients with a confirmed diagnosis of Covid-19). Safety was also assessed. RESULTS: A total of 667 patients underwent randomization; 504 patients had confirmed Covid-19 and were included in the modified intention-to-treat analysis. As compared with standard care, the proportional odds of having a higher score on the seven-point ordinal scale at 15 days was not affected by either hydroxychloroquine alone (odds ratio, 1.21; 95% confidence interval [CI], 0.69 to 2.11; P = 1.00) or hydroxychloroquine plus azithromycin (odds ratio, 0.99; 95% CI, 0.57 to 1.73; P = 1.00). Prolongation of the corrected QT interval and elevation of liver-enzyme levels were more frequent in patients receiving hydroxychloroquine, alone or with azithromycin, than in those who were not receiving either agent. CONCLUSIONS: Among patients hospitalized with mild-to-moderate Covid-19, the use of hydroxychloroquine, alone or with azithromycin, did not improve clinical status at 15 days as compared with standard care. (Funded by the Coalition Covid-19 Brazil and EMS Pharma; ClinicalTrials.gov number, NCT04322123.).
Keywords: Adult; Aged; Aged, 80 and over; Antiviral Agents; Azithromycin; Betacoronavirus; Brazil; COVID-19; Coronavirus Infections; Drug Therapy, Combination; Female; Hospitalization; Humans; Hydroxychloroquine; Male; Middle Aged; Pandemics; Patient Acuity; Pneumonia, Viral; SARS-CoV-2; Treatment Failure